Exploration of Planting Areas and Organoleptic Tests of Pineapple (Ananas comosus) in Central Aceh, Indonesia - Nasrun Liwanza; Rd. Selvy Handayani; Ismadi; Yusra; Nilahayati; Sintia Ningrum (LPPM Universitas Malikussaleh, 2022)
Pineapple (Ananas comosus) is a tropical fruit plant that is in great demand and has many benefits. Pineapple has a sweet taste slightly sour and fresh, and contains many vitamins and nutrients. Gayo pineapple is a variety originating from Central Aceh that has been certified as a national superior fruit. The problem is that the Gayo pineapple planting area is still low. This is caused by people does not know the advantages and disadvantages of Gayo pineapple compared to other national varieties of pineapple. The purpose of this study was to determine the distribution of various types of pineapple in Central Aceh as well as the level of people's preference for Gayo pineapple. This research was conducted in Pegasing District, Central Aceh Regency and at the Laboratory of Basic Agricultural Sciences, Faculty of Agriculture, Universitas Malikussaleh. the study was conducted from March to May 2022. The research used descriptive method with purposive sampling. The results showed that there were two varieties of pineapple cultivated in 5 locations in Pegasing District and its surroundings in Central Aceh, namely Gayo and Madu. Organoleptic test results showed that Gayo and Simalungun Pineapple were highly favored by consumers. Consumer preference is based on the color of the fruit flesh, aroma, taste, water content and texture of the flesh, with a score of 4.0 - 4.1 (from a standard maximum score of 5).